Trends and Determinants of Full Immunisation among Children Aged 12–23 Months - Cassocera, Marta (2023)
Funding Information: This research received funds from Global Health and Tropical Medicine (GHTM), Institute of Hygiene and Tropical Medicine (IHMT), NOVA University of Lisbon, Portugal (ref. UID/04413/2020. The funders had no role in study design, data, collection and analysis, decision to publish or preparation of the manuscript. Publisher Copyright: © 2023 by the authors.